Transformasi perdagangan internasional Indonesia: Perkembangan dan peranan perdagangan luar negeri, globalisasi, dan daya saing ekspor - Firdausi, Achmad Raihan; Shofi, Aulia Ismatul (Maliki Interdisciplinary Journal, 2024)
The development and role of Indonesia in the transformation of international trade are key to its economic progress, focusing on a shift from a commodity-based economy to one centered on investment, production, and high-value services through strategic policies. The advancement of digital technology also contributes to Indonesia's global role. Despite being influenced by global economic dynamics and geopolitical tensions, particularly between Russia and Ukraine, Indonesia faces challenges and opportunities for economic recovery and the advancement of international trade. The economic transformation of Indonesia is concentrated on the development of human resources, energy, infrastructure, transportation, public finance, industry, trade, and agriculture. The goal is to enhance international trade relations and solidify Indonesia's position as a global economic leader. Search highlights include the development of foreign trade, the crucial role of international trade, and an analysis of the impact of globalization on Indonesia's international trade. Factors such as government policies, global economic dynamics, technological progress, and environmental issues affect the growth of Indonesia's international trade. The importance of implementing policies that support sustainable economic growth and adaptation to global changes is crucial. The significant role of Indonesia's international trade serves as a driver for economic growth through import-export opportunities, resource efficiency, and investment. Collaboration between countries, technology transfer, and knowledge through international trade support diplomacy, peace, innovation, and competitiveness. The conclusion emphasizes the complexity of the role of international trade, encompassing economic, social, environmental aspects, and international collaboration to optimize global trade benefits.